Ten relevant questions for applying biodiversity offsetting in the Pantanal wetland - Reinaldo Francisco Ferreira Lourival; Fabio de Oliveira deRoque; Fábio Padilha Bolzan; Angélica Guerra; Alessandro Pacheco Nunes; Ana Cristyna Reis Lacerda; André Valle Nunes; Amanda Alves; Antônio Conceição Paranhos Filho; Danilo Bandini Ribeiro; Donald P. Eaton; Elizângela Silva Brito; et al. (Conservation Science and Practice)
Abstract In Brazil, biodiversity offsetting operates in an ad hoc manner while biodiversity equivalence has mainly been overlooked by public policies. Despite being mandatory since 1965s Forest Code (Law 4.771), we fail to have a robust offsetting framework. The revision of the forest code in 2012 (i.e., Native Vegetation Protection Law—NVPL—Law n° 12,651/2012), maintained the obligation for landowners to set aside a biome‐specific percentage of their native vegetation for preservation. Known as Legal Reserves, these set‐asides are a precondition for compliance with NVPL's regularization procedure called CAR (Rural Environmental Cadaster). Despite enthusiasm about biodiversity offsetting opportunities following the NVPL enactment in 2012, uncertainties around its implementation remains. Here, we formulated 10 questions that discuss and illustrate how offsetting can be applied to maintain wetland integrity, economic fairness and biodiversity conservation in the Pantanal and Upper Paraguay River basin (UPRB). The aim is to stimulate robust public policies and stimulate wetland offsetting research opportunities. We provided examples of implementation opportunities of the NVPL in integrating the floodplain and highland in Pantanal at UPRB, analyze spatial compliance deficits, and illustrate opportunities that require harmonized legislation and policies between Mato Grosso and Mato Grosso do Sul states in Brazil.